Postrelease exploration and stress tolerance of landlocked and anadromous Atlantic salmon and their hybrids ... - Eronen, Aslak; Hyvärinen, Pekka; Janhunen, Matti; Kekäläinen, Jukka; Kortet, Raine (Dryad, 2023)
Background We studied postrelease explorative behavior and stress tolerance of Landlocked and anadromous Atlantic salmon and their hybrids. For the research, we hybridized the Landlocked salmon of Lake Saimaa with a Baltic anadromous salmon from River Kymijoki, Southern Finland (strain originally from River Neva, Russia). These fish were hybridized in November 2017 and October 2018 in the Kainuu Fisheries Research Station, Paltamo, Kainuu, Finland (kfrs.fi).In the data the fish are treated as four strains (column 'Strain'): 1. Purebred Landlocked salmon (LLxLL), 2. hybrids, where the maternal population was landlocked salmon (LLxBA), 3. hybrids, where the maternal population was Baltic anadromous salmon (BAxLL) and 4. purebred Baltic anadromous salmon (BAxBA). Experiment 1. Post-release exploration In experiment 1., consisting of two separate trials, we studied post-release exploration of the fish in four circular seminatural streams. (Datasets 'Exploration2018.csv' & 'Exploration2020.csv', see also ... : Experiment 1. 'Figure_1.jpg' Datasets 'Exploration2018.csv' & 'Exploration2020.csv' In experiment 1., we studied post-release exploration of the hybridized salmon in four circular seminatural streams (column 'Pool'). All fish involved were identified using passive integrated transponders (column 'PIT'). Movement, or explorative behavior, of the fish in the seminatural streams was followed using four evenly spaced antennae capable of reading the fish's PIT-tags. This movement data has been summarized in the columns 'Descending' (movement with the water stream, i.e. downstream movement), 'Ascending' (upstream movement) and 'Total' (Total movement, i.e. Ascending & Descending). Units in these columns are rounds that the fish swam in the circular streams per hour (column 'Time.of.Day' and 'Pseudotime' from the start to the end of the experiment). Centerline length of the circular streams was 26.15 m and therefore the rounds can be converted to meters by multiplying by 26.15. The experiment consisted of ...